Airplane! [videorecording (Blu-Ray)] - Abrahams, Jim, 1944-; Zucker, David, 1947-; Zucker, Jerry; Koch, Howard W., Jr., 1945-; Davison, Jon, 1949 July 21-; Hays, Robert, 1947-; Hagerty, Julie; Abdul-Jabbar, Kareem, 1947-; Bridges, Lloyd; Graves, Peter, 1926-2010; Nielsen, Leslie, 1926-2010; Patterson, Lorna, 1956-; et al. (Paramount, 2022)
In this spoof of disaster movies, Ted Striker, an ex-Navy pilot, just got dumped by his long-time girlfriend Elaine Dickinson, who works as a stewardess. In his wish to get her back, he follows her aboard a plane, although he has had a deep aversion against anything winged since he lost several men in the war. During flight, he tries to make up with her again and again, but a crisis looms as the crew and many passengers get seriously ill due to a bad fish meal. Now, it is up to him to land the airplane safely, before the poisoning starts causing casualties. But Ted Striker's aversion to piloting is a serious psychosis, which breaks open and needs to be cured--right now.